The physiological and genetic basis of drought tolerance in bread wheat and ancestral wheat species - Roghzai, Yadgar Ali Mahmood (2016)
Winter wheat (Triticum aestivum L.) is the major arable crop worldwide, with a total annual global production of about 716 million tonnes and annual UK production of about 16 million tonnes from about 1.8 million hectares of land. Currently in the UK, approximately 15-20% of annual wheat yield production is lost to drought (Foulkes et al., 2002). In the present study two field experiments in 2012-13 and 2013-14 were conducted characterising a doubled-haploid (DH) population of 94 lines derived from a cross between winter wheat Rialto and Savannah. Two glasshouse experiments were conducted using four DH lines from the Rialto x Savannah DH population and the two parents, three accessions of each of three parental wheat ancestral species (T. bessarabicum, T. uratu and A. speltoides), and seven amphidiploid lines derived from crosses between durum wheat cultivars and T. bessarabicum. Two irrigation treatments were applied in both field (fully irrigated and rain-fed) and glasshouse (well-watered and water-stressed) experiments at the University of Nottingham, School of Biosciences, Sutton Bonington Campus, UK (52o 50' N, 1o 15' W). In each experiment, grain yield and above-ground dry matter partitioning were assessed at harvest, as well as a range of physiological traits at sequential assessments through the season. In the glasshouse experiments, water uptake and water-use efficiency (above-ground dry matter to total water uptake ratio) were also measured from the date of transplantation to harvest. Quantitative trait loci (QTL) analysis was carried out for the traits measured in the Rialto x Savannah DH population in the field experiments. In the field experiments, drought reduced grain yield by 22% in 2013 and by 2% in 2014. In 2013, amongst the sub-set of six DH lines and the two parents, variation for grain ∆13C, leaf photosynthetic rate, stomatal conductance and transpiration efficiency was observed (P<0.05), and flag-leaf Amax, gs and grain ∆13C were positively associated with grain yield (R2=0.55, P<0.05; R2=0.57, P<0.05, and R2=0.47, P=0.06, respectively). However, a negative relationship was found between TE and each of grain yield (R2=0.70, P<0.01) and ∆13C (R2=0.61, P<0.05) for the cross-year mean, indicating that lower TE was based on high stomatal conductance. Amongst the 94 R x S DH lines under drought, post-anthesis NDVI was positively correlated with grain yield, above-ground dry matter and TGW, and canopy temperature was negatively associated with grain yield and TGW post-anthesis (P<0.05). Late onset and end of flag-leaf senescence were associated with greater grain yield, above-ground biomass and TGW under both irrigated and drought conditions in 2013. Therefore, overall present results suggested that genetic variation in maintaining grain yield was more related to water uptake rather than WUE under mild UK water stress. In the glasshouse, the T. bessarabicum accessions had the highest flag-leaf photosynthetic rate, transpiration efficiency and SPAD associated with smaller leaf size and higher flag-leaf specific weight under drought compared with the amphidiploid lines and Rialto x Savannah DH lines. Individual amphidiploid lines had higher flag-leaf photosynthetic rate, leaf SPAD and later onset and end of flag-leaf senescence compared with the Rialto x Savannah DH lines associated with early flowering under droughted treatments. For the QTL analysis in the Rialto x Savannah DH population, a number of QTLs clusters were identified for grain yield, yield components and physiological traits under irrigated and drought conditions. Co-located QTLs were identified on chr 3A for grain yield, above-ground dry matter, thousand grain weight, plant height, anthesis date and flag-leaf senescence duration, and for stay-green traits, thousand grain weight and grains per m2. QTLs were also identified on chr 7D and 4A co-located with stay-green traits and anthesis date under irrigated and drought conditions.